Development of Electronic Student Worksheets (E-LKPD) Assisted by Liveworksheet Material for Writing Inspirational Stories for Grade IX at SMP Negeri 01 Koto Baru - Nurul Janah; Amar Salahuddin; Aprimadedi Aprimadedi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research stems from a number of issues faced at SMP Negeri 1 Koto Baru, where student worksheets (LKPD) for grade IX still use printed formats. During learning activities, especially when completing exercises, students experience difficulties and feel bored. Furthermore, students desire digital worksheets. The purpose of this research is to develop an e-LKPD for Indonesian language learning using liveworksheets on the topic of writing inspirational stories for grade IX at SMP Negeri 1 Koto Baru, which can meet the criteria of validity, practicality, and effectiveness. The type of research conducted is development research or R&D (Research and Development). The model applied in this development is the Four-D model consisting of Define, Design, Develop, and Disseminate. This process goes through four stages: first, initial analysis that includes student characteristics, concept analysis, task analysis, and setting learning objectives. The second stage is design, which compiles core competencies, basic competencies, and learning objectives. The third stage is development, which includes validation and practicality data, analysis of the practicality of student worksheets, and effectiveness results. The final stage, dissemination, is carried out using questionnaires for students, observation, and documentation. The results of this study indicate that the e-LKPD for Indonesian language learning, supported by liveworksheets on the topic of writing inspirational stories for ninth-grade students at SMP Negeri 1 Koto Baru, is highly valid, practical, and effective. The overall validity score for the e-LKPD was 85.47%, which falls into the very valid category. The practicality score for the e-LKPD, based on teacher responses, reached 86%, falling into the very practical category. The practicality score for the e-LKPD, based on student responses, also reached 88.31%, falling into the same category, which is very practical. The effectiveness test was 85.47%.